Future intensification of precipitation and wind gust associated thunderstorms over Lake Victoria - Jonas Van de Walle (Elsevier, 2021)
Severe thunderstorms affect more than 30 million people living along the shores of Lake Victoria (East Africa). Thousands of fishers lose their lives on the lake every year. While deadly waves are assumed to be initiated by severe wind gusts, knowledge about thunderstorms is restricted to precipitation or environmental proxies. Here we use a regional climate model run at convection-permitting resolution to simulate both precipitation and wind gusts over Lake Victoria for a historical 10-year period. In addition, a pseudo global warming simulation provides insight into the region’s future climate. In this simulation, ERA5’s initial and boundary conditions are perturbed with atmospheric changes between 1995–2025 and 2070–2100, projected by CMIP6’s ensemble mean. It was found that future decreases in both mean precipitation and wind gusts over Lake Victoria can be attributed to a weaker mean mesoscale circulation that reduces the trigger for over-lake nighttime convection and decreases the mean wind shear. However, an intensification of extremes is projected for both over-lake precipitation and wind gusts. The observed ∼7 %K−1 Clausius–Clapeyron extreme precipitation scaling is ascribed to increased water vapor content and a compensation of weaker mesoscale circulations and stronger thunderstorm dynamics. More frequent wind gust extremes result from higher wind shear conditions and more compound thunderstorms with both intense rainfall and severe wind gusts. Overall, our study emphasizes Lake Victoria’s modulating role in determining regional current and future extremes, in addition to changes expected from the Clausius–Clapeyron relation.